Legal Protection for Patients in Cases of Negligence of Health Workers: A Study on Private Hospitals in Indonesia - Hermawan, Dwi Bambang (Jurnal Pro Hukum : Jurnal Penelitian Bidang Hukum Universitas Gresik, 2025)
Cases of negligence of health workers in private hospitals raise serious problems related to legal protection for patients. This study aims to analyze the forms of legal protection available, the obstacles faced by patients, and alternative solutions in cases of medical negligence in Indonesian private hospitals. A qualitative approach with a case study design was used through in-depth interviews, observations, and document analysis at two private hospitals in West Java. The results of the study show that normative legal protection has been regulated in the 2023 Health Law and the Hospital Law, but its implementation is still weak. Informed consent is more practiced as an administrative formality, patient complaint units are less effective, and mediation mechanisms are rarely used. The main obstacles include low legal literacy of patients, the dominance of health workers in power relations, and the economic interests of private hospitals. This study emphasizes the need to improve patient legal literacy, legal-medical communication training for health workers, and optimize non-litigation mechanisms as a form of real protection. The implications of this study emphasize the importance of the active role of hospitals and the government in ensuring that patients' rights are protected, so that the social functions of hospitals can run in balance with business orientation.